Integrating Islamic Values In Science Education: A Case Study In Indonesian Islamic Schools - Amira Schreiber; Yusuf Wagner; Leyla Becker (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
This study explores the integration of Islamic values ​​in the science curriculum in selected Islamic schools in Indonesia. Using a qualitative case study approach, this study investigates teachers' strategies, challenges, and perceptions in integrating Islamic teachings into science lessons. Findings suggest that the integration of Islamic values ​​in science education not only enhances students' spiritual development but also promotes critical thinking skills that are in line with ethical perspectives. The paper concludes by proposing a framework to support educators in achieving a holistic approach in Islamic education.